Tracing Crime in Greenland-Set Feature Films and TV Series: Colonial Histories, Indigenous Perspectives and the Rise of Arctic Noir - Grønlund, Anders (Grønlandsk Kultur- og Samfundsforskning, 2026)
For over a century, screen narratives set in Greenland have used crime to reflect and rework tensions between law, society, and place. This article examines a broad selection of films and television series set or shot in Greenland to trace how crime is used to negotiate questions of justice, identity, and power. Through a place-based approach informed by location studies, it shows how spatial representation contributes to the narrative and symbolic role of crime across both local and international productions. While crime is used differently by Greenlandic and foreign filmmakers, the article argues that it consistently functions as a flexible narrative device for exploring Greenland’s complex social, cultural, and geopolitical realities. The conclusion identifies crime as a persistent and adaptable narrative tool, enabling filmmakers to engage with Greenland’s evolving legal, social, and geopolitical conditions.